Ulu Kasok Resort Di Desa Pulau Gadang Kabupaten Kampar Dengan Pendekatan Arsitektur Neo-Vernakular - Sayid Al-Fajri Saleh; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pulau Gadang village is one of the villages that located in Kampar of Riau province. Recently, there are many people from Riau also from other cities visited Pulau Gadang village because Ulu Kasok region has a beautiful nature. Therefore, it needs designs area to facilitate so it can develop existing potential, such as facilitation of recreation, home stay, and resort so it can increasing tourists for visits. The disign method for these designs are using approach neo-vernacular architecture by apply principles and design ideas that existing in Lontiok house by adding modern elements in it. The concept that used is transformation of return to village that result patterns of region structure, circulation that follows line and contour pattern so that the result of designs make the region become neatly and attraction it self for tourists.Key word: Resort, Lontiok House, Neo-Vernacular Architecture